Polymorphisms in microRNA binding site of SET8 regulate the risk of rheumatoid arthritis - Peng, Chenxing; Zhao, Yufei; Zhang, Xiaoyun; Zhang, Jingjing; Sha, Ziyue; Zhang, Shasha (Experimental and therapeutic medicine, 2023)
Rheumatoid arthritis (RA) is a complex, heterogeneous, progressive and long-term autoimmune disease characterized by symmetrical joint inflammation and bone erosion. The etiology of RA is unclear, but its pathogenesis is associated with oxidative stress and inflammatory cytokines. Single nucleotide polymorphisms (SNPs) in the microRNA (miRNA)-binding sites modify the development of rheumatic disease by regulating the expression of target genes. The present study investigated whether SNPs in the miRNA binding site in the 3' untranslated region (3'-UTR) of SET domain containing (lysine methyltransferase) 8 ( ) and ( ), namely rs16917496 and rs3660, respectively, were associated with the occurrence of RA. The polymerase chain reaction-ligase detection reaction assay showed that the distribution frequencies of the CC genotype (P=0.025) of SNP rs16917496 in were significantly higher in patients with RA than in healthy controls, which indicated that the CC genotype was associated with an increased risk of RA. expression in the blood samples of CC genotype carriers was lower than that of TT genotype carriers. Moreover, the CC genotype carriers exhibited higher reactive oxygen species (ROS) levels (1011.500±536.426 vs. 548.616±190.508, P=0.032) and lower interleukin-10 (IL-10) levels (P<0.001). The present study demonstrated that SNP rs16917496 in the 3'-UTR of was a predictor of RA risk and may regulate RA development by mediating expression of , thereby regulating the levels of ROS and IL-10.